Cerebral infarcts in full term neonates - (:unkn) unknown (TURKISH J PEDIATRICS, 2003)
Cerebral infarcts are an important cause of neonatal convulsions. We report the etiologic factors, and clinical and neuroradiologic findings of four full term neonates who presented with neonatal convulsions and had cerebral infarct. In our patients the risk factors for the cerebral infarct were perinatal asphyxia, sepsis, dehydration and catheter application. All had convulsions as the initial sign of infarct and had cranial imaging which revealed the definitive diagnosis. The patients underwent an extensive evaluation for hereditary causes of cerebral infarct that included anticoagulant factors (Proteins C and S, antithrombin III, antiphospholipid antibodies), factor V Leiden and prothrombin gene mutations, blood and urine amino acid and urine organic acid levels. The results were found to be within normal limits. In conclusions, neonatal convulsions can be the first sign of cerebral infarct. For this reason it seems preferable to include cranial imaging by computed tomography or magnetic resonance imaging (MRI) in the work-up of cases with unexplained neonatal convulsions.
Keywords: cerebral infarct; neonate; cranial imaging; FACTOR-V-LEIDEN; RISK-FACTOR; CEREBROVASCULAR ISCHEMIA; VENOUS THROMBOSIS; INFECTION; CHILDREN; MUTATION; INFANTS; STROKE; THROMBOPHILIA